Physical and socioeconomic driving forces of land use and land cover changes: the case of Hawassa City, Ethiopia - Tessema, Mefekir Woldegebriel; Abebe, Birhanu Girma; Bantider, Amare (Frontiers in Environmental Science, 2024)
Hawassa served as the country's southern region's capital from 1990 to 2019 and is currently experiencing rapid urbanization. Urban planners use the physical and socioeconomic driving elements of Land Use Land Cover Change (LULCC) to identify the variables influencing the trend of urbanization and then make appropriate plans.Systems and Remote Sensing to collect and analyze accurate and reliable information. The data were collected through questionnaire, interviews and key interview. Finally, the data were analyzed in different ways like figures and tables. Descriptive and econometric model are also used to analyze the data, probit regression models were used to investigate the impact of urban expansion on the livelihood of surrounding displaced farmers.FINDINGS: Multivariate analysis of variance indicated that the effect of urban expansion on the combined dependent variables, namely, on land use, socio-economic activities, culture, and environmental change is statistically significant F(8, 616) =12.704, p=0.000, Wilk's Lambda (λ) = .737, partial eta squared( partial η2)=0.142, observed power=1.000. Comparatively, the area covered by farmland, built-up, and bushland increased, from 19.46% to 26.51%, from 11.97 to 18.71%, and from 3.07% to 4.51%, respectively. The mean score for the level of social relationship and values after land expropriation was 1.7 moderate with a standard deviation of 0.852 in comparison with the mean score for the level of social relationship and values before land expropriation which was 3.21 high with a standard deviation of 0.79. This shows the land expropriation program negatively affected farmers' levels of social relationships and values high social relations before displacement and after displacement their social lay between low and moderate levels.have hindered the growth of the city and produced a serious issue with good governance in the area.